A descriptive study on the utilization of recovery methods in reducing doms symptoms post-intensive training - Anugrah, Sendy Mohamad; Triprayogo, Rian; Fathannisa, Tuliss Bial; Ramadan, Dikdik Najmu; Irsyad, Naufallathuf Yaquttul; Diana, Wulan Azva; Nuryadin, Arief (Jurnal Ilmu Keolahragaan, 2026)
Background. Delayed Onset Muscle Soreness (DOMS) is a common condition following intensive exercise, characterized by muscle pain, reduced range of motion, and increased inflammation, which can disrupt the continuity of physical activity. Although various recovery methods have been developed, a gap remains between scientific effectiveness and actual usage in practice. Objectives. This study aims to describe usage patterns and perceived effectiveness of recovery methods for alleviating DOMS symptoms, as well as to evaluate recovery duration experienced by physically active individuals. Methods. Using a descriptive quantitative approach with a cross-sectional survey design, data were collected through an online questionnaire from 60 respondents aged 18–34 years who exercised at least three times a week and had experienced DOMS in the past three months. The data were analyzed descriptively through frequency distribution and mean scores. Results. Results showed that active stretching was the most frequently used method (33%), whereas massage therapy was perceived as the most effective (mean score 4.5/5.0) and provided the fastest recovery (1 day). Supplements and cryotherapy demonstrated moderate effectiveness but had lower usage rates due to limited accessibility and awareness. Conclusion. The findings indicate a mismatch between the popularity of recovery methods and their physiological effectiveness, highlighting the importance of evidence-based education in selecting appropriate recovery strategies. This study contributes to the development of exercise physiology and training management practices and serves as a reference for designing more efficient and context-appropriate post-exercise recovery programs.